Symmetry : A Very Short Introduction - Stewart, Ian, 1945- (Oxford, New York Oxford University Press, 2013)
Ian Stewart demonstrates symmetry's deep implications, describing how symmetry's applications range across the entire field of mathematics and how symmetry governs the structure of crystals, innumerable types of pattern formation, and how systems change their state as parameters vary. Symmetry is also highly visual, with applications that include animal markings, locomotion, evolutionary biology, elastic buckling, waves, the shape of the Earth, and the form of galaxies.
Include Index and Illustration
Keywords: Symmetry (Mathematics) -- Symmetry